Adsorption isotherm, kinetic modeling and mechanism of tetracycline on Pinus taeda-derived activated biochar. (July 2018) - Jang, Hyun Min; Yoo, Seunghyun; Choi, Yong-Keun; Park, Sunkyu; Kan, Eunsung
Highlights: Pinus taeda -derived activated biochar was used for removal of tetracycline. Possible adsorption mechanisms were explained by kinetic and isotherm studies. Significant increase in adsorption capacity was achieved after NaOH activation. Intraparticle diffusion would be the major limitation for the adsorption. Adsorption capacity of activated BC was compared to commercial activated carbons. Abstract: The objective of this study was to evaluate the adsorption of tetracycline (TC) on the Pinus taeda -derived activated biochar (BC). After NaOH activation, the well-developed porous surface structure was observed with a significantly increase in surface area (959.9 m 2 /g). The kinetic and isotherm studies indicated that hydrogen bonding and π-π interaction on the heterogeneous surface would be the possible mechanisms, while intra-particle diffusion was considered as the major limitation for the adsorption of TC on the activated BC. The maximum adsorption capacity of the activated BC (274.8 mg TC/g BC) was higher than those of various activated BCs from the previous studies while it was similar to those of commercial activated carbons. It indicated that the activated BC had the high potential for TC removal in water.